A Proposed Model to Determine Public Acceptance on Willingness to Pay Maximum Demand (MD) Charge in Malaysia - Abdullah, WMZW; Zainudin, WNRA; Ramli, NA (American Scientific Publishers, 2024)
Indexed by WOS